PEMANFAATAN ZEOLIT ALAM AKTIF SEBAGAI ADSORBEN BIOETANOL AMPAS TEBU - Alsari, Nabila Estiani; Amaria, Amaria (Unesa Journal of Chemistry, 2023)
The fossil energy crisis due to the high use of fuel oil is an important factor in efforts to develop alternative energy sources from natural raw materials, namely bioethanol. Bioethanol is made from raw materials such as starch, sugar or cellulose which produces low ethanol content, so it needs to be increased through a dehydration process with activated natural zeolite. This study aims to determine the content of bagasse bioethanol and the optimal time of water adsorption in bioethanol using active natural zeolite. In this study natural zeolite was activated chemically and physically using 2% H2SO4 for 3 hours and calcined at 600?C for 6 hours. Variation in adsorption time of bioethanol with zeolite was 1, 3, 5 and 7 hours with three repetitions. Sugarcane bagasse bioethanol is produced through hydrolysis, followed by yeast fermentation, distillation and adsorption with active natural zeolite, then the ethanol content is measured with an alcohol refractometer. The results obtained were that the ethanol content of bagasse before being adsorbed was 42% and after being adsorbed with zeolite at variations of soaking time of 1, 3, 5 and 7 hours respectively 43%; 44%; 47%; and 45%.